Ability in Memorizing the Quran Amongst Housemen in Hospital Raja Permaisuri Bainun, Ipoh - Atan, Zulkefli Bin (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: To evaluate the ability in memorizing the Quran amongst the housemenand to evaluate the influence of previous educational background towards this ability. Methods: A total of 385 muslim housemen have been enrolled in the orthopaedic postingin Hospital Raja Permaisuri Bainun between May 2017 to June 2022. All of them have been recruited in the Quran memorisation program. Each houseman was required to memorise the verses they have not memorised before. The amount to memorise was optional and decided by the housemen themselves. The demographic data, previous educational background and the actual ability in memorizing the Quran for each houseman were recorded in questionnaire forms. The quantity of memorising was measured by the number of lines in the mushaf which they have memorised. Results: On average, within the four-month posting, each houseman was able to memorise 28 lines which is equivalent to about 2 pages in the mushaf. The most popular surah to be memorised were al- Mulk (30.1%), al-Kahfi (11.5%) and al-Waqiah (8.9%). Our analysis found that the level of memorisation were better amongst the housemen with the background of Islamic secondary school. On average this group memorised 39.65 lines compared to 23.95 lines for the group with conventional secondary school background (p value <0.000). Those housemen who got their degree from universities from the Arabic countries also fare better in memorising the Quran (35.09 lines compared to 25.67 lines) (p value < 0.001). Combination of these two backgrounds also revealed better memorising ability amongst the housemen (39.09 lines compared to 26.54 lines) (p value < 0.001). Conclusion: This study proved that our housemen are able to perform Quran memorisation in the housemanship training period with an average of about two pages memorisation. The ability to memorise the Quran is significantly influenced by the educational backgrounds. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S43